Theoretical and Methodological Principles of Life Quality Model Forming of Different Population Groups - Yulia Pavlova (Jan Długosz University in Częstochowa, 2019)
The topicality. The indicators of life quality are undetermined and unstandardized; the problem of determination of a single quantitative meaning of the quality of life remains unsolved. The aim of the research - to describe modern approaches to determining the quality of life and on their basis to propose a comprehensive theoretical model for the explanation of life quality phenomenon and the role of health in its formation. Methods: analysis and synthesis of scientific literature, documentary data; methods of theoretical research (analysis, synthesis, specification, classification, historical method, comparative analysis, system and structural analysis). The results: It has been proved that the quality of life is closely related to the health of human beings and it includes physical, mental and social being, considering the beliefs, expectations and world outlook. Based on the theoretical analysis and synthesis, it proposes the multicomponent structure of the quality of life, taking into account both positive and negative aspects of life, common to people of different sex, age, and state of health. Domains, sub-domains, indicators, and variables were defined as the main components of the model. Physical Component, Mental Component, Social Activity, Material Component, Development and Identity, Environment were assigned to the components of the highest level. The health-related quality of life was separated as the single part of the model. Conclusions and recommendations for further research. The theoretical model based on the principles of consistency, hierarchy, equality, determinism, unity of internal factors and external conditions was developed.